PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Alessandra Yuricha; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Funding decisions reflected through capital structures relate to the comparison of the amount of debt used by companies with equity for investment financing.Capital structure becomes the main focus for the company because good bad capital structure can affect the financial condition of the company.The study used three factors: asset structure, profitability, and size of the company as variables that affect capital expenditures.This research aims to determine the effect of the asset structure, profitability, and size of the company on the capital structure of mining sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. Sample is a mining sector company registered (listing) in IDX during the period 2014-2018 taken by purposive sampling method obtained samples as many as 17 companies. The analytical tools used in this study are multiple linear regression analyses. Based on the test results can be concluded that testing on the hypothesis of asset structure and size of the company has no effect on the capital structure.Meanwhile, the profitability hypothesis has a negative and significant effect on the capital structure.Further research can develop this research using other variables that in theory have an influence on the capital structure.